Analysis of Accountability and Transparency in Management of the Village Revenue and Expenditure Budget (APBDes) in Pakkat Hauagong Village, Humbang Hasundutan District - Simamora, Wardah T.; Dalimunthe, Ahmad Amin; Daulay, Aqwa Naser (Universitas Dehasen Bengkulu, 2023)
This study focuses on APBDes because they have a significant impact on development in the Village, with the potential to improve public services, community participation, and welfare, but there are general problems in managing village budgets related to lack of accountability and transparency and not complying with the existing provisions of the village head, which causes community protests and the need for increased oversight and control. This study aims to analyze the implementation of the management of the Village Revenue and Expenditure Budget (APBDes) in Pakkat Hauagong Village in fulfilling the principles of accountability and transparency in accordance with Permendagri No 20 of 2018. This research uses qualitative research methods by collecting data through observation, documentation and interviews. The analytical tool used is the indicators for each stage of APBDes management based on Permendagri No 20 of 2018. The results of the study show that Accountability and Transparency in APBDes Management in Pakkat Hauagong Village are in accordance with Permendagri No. 20 of 2018, it was found that the implementation of Accountability was in accordance with a percentage rate of 93% in the planning, administration, reporting and accountability stages, although there was one aspect in the implementation stage that was not fully in accordance with the provisions. Meanwhile, the implementation of Transparency is quite in accordance with the percentage level of 67%, although there are still improvements, especially related to the completeness of the information conveyed through bulletin boards and written reports.